2011
DOI: 10.1166/jnn.2011.2739
|View full text |Cite
|
Sign up to set email alerts
|

Study of DNA Interaction with Cobalt Ferrite Nanoparticles

Abstract: Interaction of cobalt ferrite nanopowder and nucleic acid was investigated. Superparamagnetic cobalt ferrite nanoparticles (6-12 nm) were prepared by mechanochemical synthesis. Structure of the nanopowder was characterized using X-ray diffraction. It was shown that cobalt ferrite nanoparticles were associated with ssDNA and dsDNA in Tris-buffer resulting in bionanocomposite formation with mass weight relation nanoparticles: DNA 1:(0.083 +/- 0.003) and 1:(0.075 +/- 0.003) respectively. The mechanism of interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…23 It was reported the interaction between CoFe 2 O 4 -NPs and nucleic acid occurred, and the linkage was based on a coordination interaction of the phosphate groups and the oxygen atoms on the heterocyclic bases of DNA with metal ions on the particle surface. 24 Also, Ahmad et al 10 pointed out the genotoxicity of CoFe 2 O 4 -NPs. Similarly, Colognato et al 25 reported the induction of genotoxicity in human peripheral lymphocytes exposed those CoFe 2 O 4 -NPs.…”
Section: Discussionmentioning
confidence: 99%
“…23 It was reported the interaction between CoFe 2 O 4 -NPs and nucleic acid occurred, and the linkage was based on a coordination interaction of the phosphate groups and the oxygen atoms on the heterocyclic bases of DNA with metal ions on the particle surface. 24 Also, Ahmad et al 10 pointed out the genotoxicity of CoFe 2 O 4 -NPs. Similarly, Colognato et al 25 reported the induction of genotoxicity in human peripheral lymphocytes exposed those CoFe 2 O 4 -NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Cobalt-ferrite nanoparticles (CoFe 2 O 4 ; 6–12 nm) were used to investigate the interaction with nucleic acid (63). The investigators in this study observed that the research data collectively revealed that there was an interaction between CoFe 2 O 4 nanoparticles and nucleic acid.…”
Section: Genotoxicity and Carcinogenicity Of Cobalt-based Nano-particlesmentioning
confidence: 99%
“…Due to these circumstances, new strategies are required to improve the antibacterial therapy. Among them, one strategy aims at the development of new drugs by re−engineering existing drugs to improve their bioavailability and antibacterial activity …”
Section: Introductionmentioning
confidence: 99%
“…Transition metals can exhibit a wide variety of coordination properties and reactivity, which can be used to form complex with organic drugs as ligands. Transition metal complexes exhibit unique and interesting properties such as changing oxidation states and the ability to form specific interactions with other biomolecules . Thus the coordination of some metals with antibiotics would prevent development of resistance by microbes, enabling novel mechanisms of action and enhance the antimicrobial property of the antibiotic .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation